Mycophenolic acid AUC in Thai kidney transplant recipients receiving low dose mycophenolate and its association with UGT2B7 polymorphisms - Pithukpakorn M; Tiwawanwong T; Lalerd Y; Assawamakin A; Premasathian N; Tasanarong A; Thongnoppakhun W; Vongwiwatana A (Dove Medical Press, 2014)
Manop Pithukpakorn,1 Tiwat Tiwawanwong,2 Yupaporn Lalerd,3 Anunchai Assawamakin,3,4 Nalinee Premasathian,2 Adis Tasanarong,5 Wanna Thongnoppakhun,3 Attapong Vongwiwatana2 1Division of Medical Genetics, 2Division of Nephrology, Department of Medicine, 3Division of Molecular Genetics, Department of Research and Development, Faculty of Medicine Siriraj Hospital, 4Department of Pharmacology, Faculty of Pharmacy, Mahidol University, 5Department of Medicine, Faculty of Medicine, Thammasat University, Bangkok, Thailand Background: Despite use of a lower mycophenolate dose in Thai kidney transplant patients, acceptable graft and patient outcomes can be achieved. We therefore examined the pharmacokinetics of mycophenolic acid (MPA) by area under the curve (AUC) and investigated genetic contribution in mycophenolate metabolism in this population. Methods: Kidney transplant recipients with stable graft function who were receiving mycophenolate mofetil 1,000 mg/d in combination with either cyclosporine or tacrolimus, and prednisolone were studied. The MPA concentration was measured by fluorescence polarization immunoassay (FPIA), at predose and 1, 1.5, 2, 4, 6, 8, 10, and 12 hours after dosing. Genetic polymorphisms in UGT1A8, UGT1A9, and UGT2B7 were examined by denaturing high-performance liquid chromatography (DHPLC)-based single-base extension (SBE) analysis. Results: A total 138 patients were included in study. The mean AUC was 39.49 mg-h/L (28.39–89.58 mg-h/L), which was in the therapeutic range. The correlation between the predose MPA concentration and AUC was poor. The mean AUC in the tacrolimus group was higher than that in the cyclosporine group. Polymorphisms in UGT2B7 showed significant association with AUC. Conclusion: Most of our patients with reduced mycophenolate dose had the AUC within the therapeutic range. Genetic polymorphisms in UGT2B7 may play a role in MPA metabolism in Thai kidney transplant patients. Keywords: UGT, MPA, pharmacokinetic, immunosuppressive